7-4x+3x-5=6x+1+2x-3

Simple and best practice solution for 7-4x+3x-5=6x+1+2x-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7-4x+3x-5=6x+1+2x-3 equation:


Simplifying
7 + -4x + 3x + -5 = 6x + 1 + 2x + -3

Reorder the terms:
7 + -5 + -4x + 3x = 6x + 1 + 2x + -3

Combine like terms: 7 + -5 = 2
2 + -4x + 3x = 6x + 1 + 2x + -3

Combine like terms: -4x + 3x = -1x
2 + -1x = 6x + 1 + 2x + -3

Reorder the terms:
2 + -1x = 1 + -3 + 6x + 2x

Combine like terms: 1 + -3 = -2
2 + -1x = -2 + 6x + 2x

Combine like terms: 6x + 2x = 8x
2 + -1x = -2 + 8x

Solving
2 + -1x = -2 + 8x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-8x' to each side of the equation.
2 + -1x + -8x = -2 + 8x + -8x

Combine like terms: -1x + -8x = -9x
2 + -9x = -2 + 8x + -8x

Combine like terms: 8x + -8x = 0
2 + -9x = -2 + 0
2 + -9x = -2

Add '-2' to each side of the equation.
2 + -2 + -9x = -2 + -2

Combine like terms: 2 + -2 = 0
0 + -9x = -2 + -2
-9x = -2 + -2

Combine like terms: -2 + -2 = -4
-9x = -4

Divide each side by '-9'.
x = 0.4444444444

Simplifying
x = 0.4444444444

See similar equations:

| n^2-18n+72=0 | | .15x-3=0.4(x-5) | | 26=r*13 | | x+10x+4=180 | | 4x+1+5-2x+3x=2x-5+x | | 15=t^2+2t | | 8x-12=-5x+27 | | 7y+4y-8=80 | | -5x+1=y | | .2x+.3(x+1)=2 | | 6x^2-2=-50 | | y[n]+0.4y[n-1]=3x[n] | | (X-11)(7x+1)=0 | | 3+30x=15x+30 | | 6x+3y=9fory | | 1/5x-3=-6 | | Ln(3x-2)=10 | | 14A+13B-6A+7= | | 10=12-8 | | 4+4=-6 | | y=3-1/2x | | 5(a-1)-4(a-2)=2(5a+20) | | 10=2x-86 | | F(9)=3 | | 1000=r^3/2 | | 3(X+2X)+9R= | | 20y+3x=50 | | ((3y+4)*2)+((y+3)*2)=70 | | .5n+15=3n | | (X+5)(x+5)-49=0 | | -12=w+18 | | 5z-18-z+2= |

Equations solver categories